The role of stakeholders in Solomon’s Temple: an exploratory study - Bazanini, Roberto; Giglio, Ernesto Michelângelo (Escola de Administração da Universidade Federal da Bahia, 2017)
This paper aims to describe the role of stakeholders in the symbolic goods market of religion. Drawing on qualitative research, and based on the salience model of stakeholders, the objective is to analyze the importance of Solomon’s Temple megachurch to the Universal Church of the Kingdom of God (UCKG) as a competitive factor in the market of religious goods and services for achieving a competitive advantage. The findings show that the respondents’ perception indicates that the construction of megachurches provides a competitive advantage if the stakeholders are identified and continuously monitored because of the attributes of power, legitimacy and urgency. The contribution of the study is a discussion on the relevance of the applicability of stakeholder theory in the symbolic goods market of religion from the perspective of network relationships with other stakeholders.

Esse artigo descreve a atuação dos stakeholders no mercado de bens simbólicos da religião. Por intermédio de pesquisa exploratória, de natureza qualitativa, o objetivo da pesquisa está em analisar a importância desse megatemplo para a Igreja Universal do Reino de Deus (IURD) como empresa inserida no concorrencial de bens e serviços religiosos para o alcance de vantagem competitiva. Os resultados da pesquisa mostram que a criação de megatemplos pode ser concebida uma situação real de mercado competitivo capaz de influenciar as estruturas de organizações religiosas pela visibilidade política e da mídia que ele proporciona. A contribuição da pesquisa está em discutir a pertinência da aplicabilidade da teoria dos stakeholders no mercado de bens simbólicos da religião por permitir estudar a criação dos megatemplos como estratégia de marketing a partir da perspectiva de redes de relacionamentos com outros atores.
O papel dos stakeholders no Templo de Salomão: um estudo exploratório
Keywords: Stakeholder theory; Network relationships; Marketing strategies; Megachurches; Teoria dos stakeholders; Redes de relacionamento; Estratégias de marketing; Megatemplos